Characterization and dissolution studies of Furosemide solid dispersions using polyethylene glycol (PEG), talc and PEG-talc as dispersion carriers - Yandi Syukri; Diny Rizayulianty; Yuni Darty (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2004)
Solid dispersions of furosemide were prepared by melting and solvent methods using polyethylene glycol (PEG) 6000, talc and PEG – talc as dispersion carrier in order to improve furosemide dissolution. The increase of dissolution and physical properties of its powder was evaluated. Only furosemide solid dispersions with combination of PEG – talc 1 : 3 showed a good physical properties. The assay of the effect of PEG – talc ratio on furosemide dissolution showed that the increase of ratio of PEG – talc increased significantly dissolution rate.Key Word : furosemide, solid dispersion, dissolution